2011
DOI: 10.1163/001121611x574290
|View full text |Cite
|
Sign up to set email alerts
|

South African Pelagic Goose Barnacles (Cirripedia, Thoracica): Substratum Preferences and Influence of Plastic Debris on Abundance and Distribution

Abstract: Twenty-two South African shores were surveyed for stranded debris colonized by goose barnacles. The most frequently colonized substrata were kelp (Ecklonia maxima) and plastic, comprising 33.1 and 29.0% of total colonized items, respectively. Four goose barnacle species showed significant preferences for specific substrata: Dosima fascicularis for feathers; Lepas anserifera for rubber sandals; L. pectinata for the shells of dead cephalopods Spirula spirula; and L. testudinata for kelp E. maxima. The other spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…The efficiency of rafting dispersal depends on the availability and the persistence of floating substrata in the oceans. Already established populations may disperse regionally with the help of marine litter, as was observed by Whitehead et al (2011) for lepadid barnacles in South Africa, by Serrano et al (2013) for a Mediterranean population of the coral Oculina patagonica and also by Davidson (2012) for the isopod Sphaeroma quoianum, which "manufactures" its own raft by causing fragmentation of Styrofoam/polystyrene dock floats.…”
Section: Floating Litter As Dispersal Vectormentioning
confidence: 94%
See 1 more Smart Citation
“…The efficiency of rafting dispersal depends on the availability and the persistence of floating substrata in the oceans. Already established populations may disperse regionally with the help of marine litter, as was observed by Whitehead et al (2011) for lepadid barnacles in South Africa, by Serrano et al (2013) for a Mediterranean population of the coral Oculina patagonica and also by Davidson (2012) for the isopod Sphaeroma quoianum, which "manufactures" its own raft by causing fragmentation of Styrofoam/polystyrene dock floats.…”
Section: Floating Litter As Dispersal Vectormentioning
confidence: 94%
“…Wong et al (1974) did not find algae and invertebrates on plastic fragments, which were significantly smaller than floating pumice in the Goldstein et al 2014) same region. Lepadid barnacles seem to have species-specific preferences for litter of certain size, and some species (Lepas pectinata and Dosima fascicularis) associated with smaller litter items develop morphological adaptations, such as a small body size and light-weight valves, that minimize the risk of sinking of colonized flotsam (Whitehead et al 2011). A size-specific selection of floating substrata has previously been shown for lepadid barnacles rafting on tar pellets (Minchin 1996).…”
Section: Floating Litter As a Habitatmentioning
confidence: 95%
“…biofilms) (yet see Winston et al 1997, Lobelle & Cunliffe 2011. Introduced species have a higher propensity to foul man-made substrates, such as plastics (Whitehead et al 2011), than native species (Wyatt et al 2005, Glasby et al 2007, Tamburri et al 2008. Couple this propensity with the durability and persistence of plastics, and the likelihood of plastics transporting non-native species increases substantially.…”
Section: Priority Research Questionsmentioning
confidence: 99%
“…Ye & Andrady 1991, Artham et al 2009) with the type of substrate and the distance from source areas (and hence residence time at sea). For example, Whitehead et al (2011) determined that of stranded debris in South Africa, kelp and plastics were the most frequently colonized (33 and 29%, respectively). In contrast, Widmer & Hennemann (2010) reported that only 5% of marine debris was biofouled in southern Brazil (27°S), of which 98% of the items were plastic (Widmer & Hennemann 2010).…”
Section: Priority Research Questionsmentioning
confidence: 99%
“…This fact suggests that the abundance of the species could be increased after the spills, providing numerous floating surfaces for attachment. Whitehead et al (2011) also conclude that the increasing abundance of plastic (or other available substrata) is drastically increasing the opportunities for the goose barnacles to colonize and it greatly influences their abundance and distribution. …”
Section: Juan Junoymentioning
confidence: 91%